Release kinetics of growth factors loaded into β-TCP ceramics in an in vitro model - Waldmann, Marco; Bohner, Marc; Baghnavi, Anna; Riedel, Bianca; Seidenstuecker, Michael (Frontiers in Bioengineering and Biotechnology, 2024)
β-TCP ceramics are bone replacement materials that have recently been tested as a drug delivery system which can potentially be applied to endogenous substances like growth factors found in blood platelets to facilitate positive attributes. In this work, we used flow chamber loading to load β-TCP dowels with blood suspensions of platelet-rich plasma, platelet-poor plasma or buffy coat character. PRP and BC platelet counts were adjusted to the same level by dilution. Concentrations of TGF-β1, PDGF-AB and IGF-1 from dowel surrounding culture medium were subsequently determined by means of ELISA over a time of 5 days. Influence of alginate was additionally tested to modify release. Concentrations of TGF-β1 and PDGF-AB increased and conclusively showed a release from platelets in PRP and BC compared to PPP.Alginate coating reduced PDGF-AB release but did not reduce TGF-β1 and instead even increased TGF-β1 in BC samples. IGF-1 concentrations were highest in PPP, suggesting circulating levels rather than platelet release as the driving factor. Alginate samples tended to have lower IGF-1 concentrations but could not be shown to be significant.Conclusively, the release of growth factors from different blood suspensions could be successfully demonstrated for β-TCP as a drug delivery system with release patterns that correspond to PRP activation after Ca 2+ triggered activation. The release pattern was partially modified by alginate coating.